2022
DOI: 10.7719/irj.v19i1.837
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and Language Proficiency of College Students at Catanduanes State University Panganiban Campus

Abstract: The study determined the attitudes toward the English language, the general proficiency level of 60 selected first-year college students, language structure, reading comprehension, and vocabulary. This was conducted to solve current issues of reading comprehension difficulties and poor linguistic competence in English subjects. It utilized descriptive research. Findings revealed “zero highly unfavorable” attitudes towards English; 2 “highly favorable.” For language structure, half of them were “slightly profic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…In addition, senior high school students' low level of reading problems indicated that students were rarely having reading problems. These findings supported the claim that the Philippines' English atmosphere improved as students could use English across various social contexts ( [53,54].…”
Section: Level Of English Language Problemssupporting
confidence: 80%
“…In addition, senior high school students' low level of reading problems indicated that students were rarely having reading problems. These findings supported the claim that the Philippines' English atmosphere improved as students could use English across various social contexts ( [53,54].…”
Section: Level Of English Language Problemssupporting
confidence: 80%
“…The profile includes age, sex, educational qualification/ attainment, years in service as school heads, and the number of training attended. The variables are attributed to Salvador (2015).…”
Section: Instrumentationmentioning
confidence: 99%
“…Data on challenges had been adapted from the published study by Castroverde and Acala (2021). The measures used were a four-point scale coded 4-Serious Problem; 3 -Moderate Problem; 2-Slight Problem, and 1 -Not a Problem adapted from the study of Salvador (2015).…”
Section: Instrumentationmentioning
confidence: 99%